The Baldwin locomotive works 1831 - 1915 ; a study in American industrial practice - Brown, John K. (Studies in industry and society, 1995)
The largest maker of heavy machinery in Gilded Age America and an important global exporter, the Baldwin Locomotive Works of Philadelphia achieved renown as one of the nation's most successful and important firms. Relying on skilled craftsmen in labor-intensive batch production, Baldwin made the heavy machinery that transformed the United States into the world's top industrial power in the late nineteenth and twentieth centuries. In The Baldwin Locomotive Works, 1831-1915, John K. Brown combines economic, business, labor, and social history and the history of technology to write a dazzling account of this giant of nineteenth-century industry. Comprehensive and heavily illustrated, Brown's study analyzes the structure of railroad demand; the forces driving continual innovation in locomotive design; Baldwin's management systems, shop-floor skills, and career paths; and the evolution of production methods. Baldwin's sophisticated production-management controls prefigured the scientific management movement and allowed the firm to fulfill its customers' special design needs, thus cementing close relations with clients. The company became so adept at meeting varied specifications that in a single year, 1890, its 4,500 workers made 946 locomotives to 316 different designs.